Semiotics of Senses in the Holy Quran - كاظم, جنان منصور; حميد, عبد السلام (ALBAHITH ALALAMI, 2016)
This study is based on the basic idea: that human communication does not stop at the limits of words spoken, but extends to include the movements of the body and its members, such as the face, hand, eye, hearing, touch, taste, sensation and the public body.The human movements represented by polarization, frowns, tattoos, and movements are all auxiliary tools that reach meanings and affect others greatly. Perhaps their importance is also in their ability to translate what is going on in the soul, and to show it to the outside body members, without the control of the human in many cases, it is thus an important factor in the process of human communication.The purpose of this study is to show the senses of the senses in the Holy Quran by presenting the verses that refer to the functions of the senses to show their symbolic semantic, verbal or nonverbal communication that expresses consciousness or unconsciousness.The study examines how the senses in the Holy Quran are used symbolically. The senses are considered to be the source of reason for the external world, which represents a field of reflection, reflection and awareness of abstract meanings. We review and analyze Quranic evidence that proves that the Holy Quran spoke about this subject, and dealt with it with some rooting and depth, and this is like the Holy Quran, the net spring of all sciences, which we should always refer to to get rid of a certain.